The Potential of Platelet-Rich Plasma in Promoting Axonal Regeneration: A Narrative Review - Meutia Maulina; Yuziani; Rizka Sofia (Faculty of Medicine University of Malikussaleh, 2024)
Platelet-rich plasma (PRP) is an autologous blood product obtained by centrifugation. PRP is characterized by a high concentration of growth factors, which are known to promote tissue healing, influence angiogenesis, and exhibit immunomodulatory effects without causing significant adverse reactions. Consequently, PRP has been used in various medical specialties, including neurology, in recent years. This review aimed to provide an overview of the current evidence on the use of PRP to promote axonal regeneration. An extensive literature search was conducted across several databases, including PubMed and Google Scholar, using keywords such as platelet-rich plasma (PRP), platelet-concentrated plasma, platelet-rich growth factors, and axonal regeneration. A detailed analysis of the relevant studies was performed, and the data were meticulously extracted and analyzed. Studies have indicated that PRP may have promising potential to facilitate nerve regeneration. Specifically, PRP has been shown to be effective in protecting nerves, preventing neuronal apoptosis, and stimulating vascular and axonal regeneration. Furthermore, PRP regulates inflammatory responses in the microenvironment, which may further contribute to its potential benefits in nerve regeneration. Understanding the biology, mechanism of action, classification of PRP, and its role in axonal regeneration is crucial for clinicians to gain a complete understanding of this therapeutic approach and appropriately interpret available data on PRP.